APLIKASI PENGELOLAAN LABORATORIUM TEKNIK SIPIL UNIVERSITAS BINA DARMA BERBASIS WEB - Novita Sari, Diah; Prawira, Wanda Yudha; Anugraha, Nurhajar (JURNAL TELISKA, 2024)
A laboratory is a place equipped with equipment to carry out tests or experiments. This research aims to create an application for borrowing tools in the civil engineering laboratory at Bina Darma University so that the laboratory data processing system becomes more effective and efficient. This application was designed using UML (Unified Modeling Language) modeling, MySQL, PHP programming language with waterfall model. The result of this research is a laboratory management application which consists of recording, borrowing and returning laboratory equipment. Application testing uses black-box testing techniques.